Endovascular Treatment of Isolated Chronic Abdominal Aortic Dissection - Machado, Rui (2016)
Isolated acute abdominal aortic dissection is a relatively rare event. Its natural history is not fully understood and its optimal treatment is not established. Open surgery represents the most described treatment but endovascular intervention has had increasing application. Isolated chronic abdominal aortic dissection  is even less described in the literature. We describe three patients with isolated chronic abdominal aortic dissection who underwent endovascular treatment in our institution. Mean age at presentation was 82 years. Indication for surgical intervention was aneurismal degeneration. Mean aortic diameter at presentation was 46.7 mm. There was no perioperative mortality or reinterventions. Mean follow-up was 5.3 years (2-12 years). Late reintervention was needed in one patient, eight years after initial surgery, due to type 1 endoleak. According to our experience, endovascular intervention represents an effective and durable treatment option in isolated chronic abdominal aortic dissection. However, long-term follow-up is mandatory. Furthermore, larger studies are still needed to understand this disease and its adequate treatment.